ART, MEDIA AND SOCIAL CHANGE: EVALUATING THE AESTHETIC IMPACT OF GOVERNMENT SCHEME ADVERTISEMENTS ON RURAL WOMEN’S EMPOWERMENT - Prasad, Deepak; Mishra, Pranav; Mishra, Swayam Prava; Gupta, Anshita; Kataria, Ketan Kumar; Kumar, Sushant (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Communication programs by the government are significant in creating awareness regarding the welfare programs and empowerment programs especially in rural areas whereby the access to formal sources of information is not as high. Advertisements in the public are often based on visual media and artistic components that enable people to convey policy messages in a way that is interesting and easy to understand. These campaigns cannot be effective unless the information that is presented is accurate plus the aesthetic design of the communication. Visual composition, color scheme, cultural imagery, and storytelling are some of the elements that determine the interpretation and memorability of advertisement messages to audiences. Most of the government welfare programs such as financial inclusion programs, healthcare programs, entrepreneurship support systems, and the education development policies have rural women as a central target group. The levels of awareness and participation in such programs however are not constant in the rural areas. This paper is an investigation of the aesthetic effect of the government scheme advertisements in raising awareness and empowerment among women in the rural areas. To gauge the audience engagement, use of advertisement content analysis, survey data collection and perception evaluation was used as a mixed-method approach. Findings show that adverts with culturally familiar images, well defined stories, and emotionally interesting visual presentation are much more effective in creating awareness and recalling the message than the ones that are based purely on information. The results indicate that incorporating art-based communication practices in governmental advertising can be used to elevate the efficiency of the empowerment message and increase the social influence of the communicational message of the public policy.